2022
DOI: 10.1039/d2bm01308h
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the applications of carbon-based nanostructures in wound healing: from antibacterial aspects to cell growth stimulation

Abstract: A wound is defined as damage to the integrity of biological tissue, including skin, mucous membranes, and organ tissues. The treatment of these injuries is an important challenge for medical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 219 publications
(192 reference statements)
1
22
0
Order By: Relevance
“…Hb was then decorated onto the nanosheets using PDA coating as the chemical linkage, finally forming BC-PDA-Hb (BCPH) NSs. Compared with previous work, 45,46 the formed BCPH NSs had no fluorescent emission, good photothermal conversion performance, excellent PA imaging capability, and strong Fenton reaction activity. The Fe 2+ carried in Hb can convert H 2 O 2 overexpressed in tumor microenvironment (TME) to toxic • OH, eliminating tumor cells via CDT.…”
Section: ■ Introductionmentioning
confidence: 67%
“…Hb was then decorated onto the nanosheets using PDA coating as the chemical linkage, finally forming BC-PDA-Hb (BCPH) NSs. Compared with previous work, 45,46 the formed BCPH NSs had no fluorescent emission, good photothermal conversion performance, excellent PA imaging capability, and strong Fenton reaction activity. The Fe 2+ carried in Hb can convert H 2 O 2 overexpressed in tumor microenvironment (TME) to toxic • OH, eliminating tumor cells via CDT.…”
Section: ■ Introductionmentioning
confidence: 67%
“…There was evidence that GO-based materials could enhance cell adhesion, growth, and proliferation; these materials have been used in the fields of wound healing, tissue engineering scaffolds, and drug-delivery systems. 77,78 However, a few studies showed that SGO formed by prolonged ultrasonic treatment was easier to internalize and induce oxidative stress or irreversible cell damage without causing significant proliferation changes in cells. 7,79 Therefore, we further evaluated cellular oxidative stress injury using the DCFH-DA assay.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, conductive hydrogels can simulate the physiological environment of electroactive tissues, regulate the spinal cord microenvironment, and reconstruct the signal transduction pathway of damaged nerves, thus promoting nerve regeneration. Currently, a variety of conductive materials, such as polyaniline (PANI), polypyrrole (PPy), polythiophene (PTH), metal nanoparticles and carbon-based materials, have been introduced to construct conductive hydrogels [15][16][17][18][19]. Among them, PANI is widely used in tissue engineering because of its reasonable structural design, good water solubility and good electrical activity.…”
Section: Introductionmentioning
confidence: 99%